Optimalisasi Pemberian Edukasi pada Pasien dan Keluarga Melalui Terbentuknya Tim Perawat Edukator di Rumah Sakit: A Pilot Study - Yuyun Setiyawati; Rr. Tutik Sri Hariyati; Siti Anisah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the role of nurse educators in optimizing the provision of education in order to increase patient and family knowledge about health so as to improve quality of life. The method used is a pilot study design using a problem solving approach. The innovation program was implemented on 32 nurse educators who were recruited by purposive sampling. The evaluation stage of the FGD implementation and analysis was carried out descriptively. The results showed that the role of nurse educator is needed in an effort to improve the quality of providing education to patients and families. The innovation program carried out is the creation of a nurse educator team guide. The results of the FGD evaluation on nurse educators are the need for uniform documentation of providing individual and group education, nurse educators completing educational points according to competence, the need for competent nurse educators, mentoring and mentoring for junior nurses. In conclusion, the quality of nursing services can be increased by having a team of nurse educators. Keywords: Patient and Family Education, Nursing Services, Nurse Educator